92.4k views
11 votes
Solve for y: 2(3y + 5) = 3 (5y +1/3).

User Crypth
by
5.0k points

2 Answers

6 votes

Answer:

2(3y + 5) = 3 (5y +1/3)

6y+10=15y+1

9=9y

y=1

User Elbimio
by
4.8k points
6 votes

Answer:

y = 1

Explanation:

Step 1: Distribute

We have to distribute the coefficient to the terms in the parentheses.

2(3y + 5) = 3(5y + 1/3)

2(3y) + 2(5) = 3(5y) + 3(1/3)

6y + 10 = 15y + 1

Step 2: Isolate a term with the variable

We want one term that contains x on one side (preferably the largest value)

We can subtract 1 to isolate 15x

6y + 10 = 15y + 1

6y + 9 = 15y

Step 3: variable - term on one side, numbers on the other

Now we just want to have a value equal to the y - term (preferably largest)

Subtract 6y from both sides

6y + 9 = 15y

9 = 9y

Step 4: Isolate the variable

Now we just want the variably on one side.

We can rewrite 9y as 9 * y, and use the operation division to isolate y

9 = 9 * y

9/9 = y

1 = y

y = 1

-Chetan K

User RekoDolph
by
5.6k points